Composition operators on Hilbert spaces of entire Dirichlet series - Hou, Xiaolu. (2013)
In this Note, we introduce Hilbert spaces of entire Dirichlet series (with real frequencies) and consider composition operators on these spaces. We establish necessary and sufficient conditions for such series to have Ritt order zero, as well as a finite logarithmic order. Criteria for action, boundedness, compactness and compact difference of such operators are obtained.